Dinâmica da composição florística e fitossociologia de comunidade arbórea do Cerrado stricto sensu sob efeito da queima prescrita no Parque Nacional da Chapada dos Guimarães – MT. - Gilioli, Tatiane Pereira (2024)
Fire is an important ecological agent in the Cerrado, with records of its presence dating back millions of years. During this period, the organisms inhabiting these areas have developed various strategies to coexist with fire, with some even benefiting from this process. Therefore, the objective of this study is to evaluate the effects of fire from a prescribed burn on the ecosystem dynamics of a Cerrado stricto sensu in the Chapada dos Guimarães National Park - MT. The study aims to answer the following question: Is floristic diversity affected postprescribed burn? Data collection was conducted in a prescribed burn block of Cerrado stricto sensu located in the south-central region of Mato Grosso, in the municipality of Chapada dos Guimarães, Chapada dos Guimarães National Park. A forest inventory was carried out before the prescribed burn and another inventory after the burn. For the vegetation inventory, ten permanent plots of 10x100 meters (1,000 m²) were randomly allocated in the block. All individuals of the shrub-tree stratum, with a diameter equal to or greater than 5 cm at a height of 30 cm from the ground, were inventoried in an area of 1 hectare, with data collected on height, diameter, and species. To assess regeneration, ten 2x2 meter (4 m²) subplots were systematically allocated in each sampled permanent plot, and all individuals of the regenerating stratum, with a diameter equal to or greater than 2 cm and less than 5 cm, at a height of 30 cm from the ground, were measured for height and species. Before the prescribed burn, 59 species belonging to 28 families were identified, with a density of 1,081 individuals per hectare and a basal area of 4.14 m²/ha. After the prescribed burn, the values found were 48 species and 22 families, with a density of 948 individuals per hectare and a basal area of 4.04 m²/ha. The Shannon-Wiener diversity index was 3.22 for the first survey. After the prescribed burn, the value found for the Shannon-Wiener diversity index was 3.11. Regarding botanical families, only five, Fabaceae, Myrtaceae, Melastomataceae, Vochysiaceae, and Apocynaceae, in that order, held more than 50% of the IVI - Importance Value Index. Fabaceae was the richest and most abundant family in the fragment. The results of this study indicate that diversity was affected, with a reduction in the number of botanical families in the tree component, and consequently, a reduction in the number of genera and species. However, from a floristic perspective, it is possible to infer that the population sizes are not discrepant, as the values found before and after the fire can be compared to ecosystems with the same physiognomy under undisturbed conditions. This highlights the importance of continuing this and other research to observe the recovery dynamics of these environments.